United Arab Emirates : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
In this paper, the following statistical data of the United Arab Emirates are presented: sectoral origin of GDP at constant prices, real growth by economic sector, sectoral distribution of nominal GDP, use of resources at current prices, per capita GDP and distribution of GDP at factor cost by the Emirates, oil and natural gas production, exports and prices, average crude oil prices, agricultural production, population of the Emirates, sectoral distribution of civilian employment, pension fund operations, Abu Dhabi development expenditures, Dubai government operations, interest rates and balance of payments, and direction of trade.